2018
DOI: 10.14715/cmb/2018.64.5.12
|View full text |Cite
|
Sign up to set email alerts
|

RASSF7 promotes cell proliferation through activating MEK1/2-ERK1/2 signaling pathway in hepatocellular carcinoma

Abstract: The Ras-association domain family (RASSF) proteins have been involved in many important biological processes. RASSF7 is recently reported to be up-regulated in several types of cancer. However, the function of RASSF7 remain unknown in human cancers. To explore the role of RASSF7 in hepatocellular carcinoma (HCC) cells proliferation and molecular mechanism. RASSF7 expression was examined using public database TCGA, qRT-PCR and Western blot. The correlation between RASSF7 and clinicopathological features was mea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
10
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 42 publications
0
10
0
Order By: Relevance
“…Previous studies have demonstrated that RASSF7 is up-regulated in hepatocellular carcinoma (HCC) 34 and non-small cell lung cancer 35 . Moreover, RASSF7 overexpression is signi cantly associated with increased serum alpha-fetoprotein levels, poor tumor histology, and T staging in HCC patients; overexpression of RASSF7 promotes the proliferation of HCC cells and cell cycle transformation in the G1-S phase, and inhibit cell apoptosis, whereas down-regulation of RASSF7 gene inhibits cell growth and induces cell cycle arrest and apoptosis in G1-S phase 34 . Although the present study indicates that RASSF7 might be used as a prognostic biomarker for gastric cancer, further clinical studies are needed to con rm its prognostic value.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have demonstrated that RASSF7 is up-regulated in hepatocellular carcinoma (HCC) 34 and non-small cell lung cancer 35 . Moreover, RASSF7 overexpression is signi cantly associated with increased serum alpha-fetoprotein levels, poor tumor histology, and T staging in HCC patients; overexpression of RASSF7 promotes the proliferation of HCC cells and cell cycle transformation in the G1-S phase, and inhibit cell apoptosis, whereas down-regulation of RASSF7 gene inhibits cell growth and induces cell cycle arrest and apoptosis in G1-S phase 34 . Although the present study indicates that RASSF7 might be used as a prognostic biomarker for gastric cancer, further clinical studies are needed to con rm its prognostic value.…”
Section: Discussionmentioning
confidence: 99%
“…The detailed regulatory mechanisms are still unknown. Rassf7 has been shown earlier to regulate FGF/MEK/ERK signaling through binding to RAS proteins (Wang et al , 2016; Zhang et al , 2018a). Remarkably, the RAS‐regulated ERK signaling is also vital for the spindle orientation during lung tube development, suggesting a similar role of FGF during spindle polarity establishment (Tang et al , 2011).…”
Section: Discussionmentioning
confidence: 99%
“…RASSF7 has been suggested to play a role during mitosis through regulating microtubule dynamics (Sherwood et al , 2008; Recino et al , 2010; Gulsen et al , 2016). RASSF7 can promote cell proliferation through MEK1/2‐ERK1/2 signaling pathway activation (Wang et al , 2016; Zhang et al , 2018a). In vitro studies have also showed that, through interaction with N‐RAS, RASSF7 inhibits mitogen‐activated protein kinase kinase (MKK) 7 phosphorylation to negatively regulate pro‐apoptotic JNK signaling under stress‐induced conditions (Takahashi et al , 2011).…”
Section: Introductionmentioning
confidence: 99%
“…The N-terminal RASSF genes participate in numerous vital biological progresses, such as cell survival, apoptosis, tumor growth, and metastasis [ 7 ]. In addition, previous reports in the literature show RASSF7 expression is increased in NSCLC [ 10 ] and hepatocellular carcinoma [ 11 ] and plays a role in stimulating tumor proliferation. On the contrary, RASSF8 and RASSF10 have been shown to be reduced in multiple cancers, including lung cancer, gastric cancer, cervical cancer, breast cancer, colorectal esophageal squamous cell carcinoma, and hepatocarcinoma, and thus are considered as tumor suppressors [ 12 – 21 ].…”
Section: Introductionmentioning
confidence: 92%